2021
DOI: 10.1136/bmjsem-2020-001021
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high-intensity interval training for weight loss in adults with obesity: a randomised controlled non-inferiority trial

Abstract: IntroductionObesity treatment guidelines suggest moderate-intensity continuous training (MICT), but the patient’s compliance to this indication remains low. High-intensity interval training (HIIT) is a time sparing training mode whose metabolic effects are not clear. This study aimed to determine whether a 12-week HIIT was more effective than MICT for weight loss in obese adults.Methods44 obese subjects were randomised and trained with isoenergetic treadmill exercises for 12 weeks: MICT (60% of maximal oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Similarly, a previous study found that a 12-week exercise intervention (3 × 90 min exercise session per week) had positive effects on cardiorespiratory fitness, muscular endurance, and body composition in overweight and obese adults [ 55 ]. In addition, another study showed that an exercise intervention using two modalities (continuous and interval training) induced weight loss, reduced BMI, and increased cardiorespiratory fitness in obese subjects [ 56 ]. The results could be explained by the fact that exercise training increases resting energy expenditure, lipid oxidation, and mitochondrial capacity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous study found that a 12-week exercise intervention (3 × 90 min exercise session per week) had positive effects on cardiorespiratory fitness, muscular endurance, and body composition in overweight and obese adults [ 55 ]. In addition, another study showed that an exercise intervention using two modalities (continuous and interval training) induced weight loss, reduced BMI, and increased cardiorespiratory fitness in obese subjects [ 56 ]. The results could be explained by the fact that exercise training increases resting energy expenditure, lipid oxidation, and mitochondrial capacity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this secondary analysis aimed at studying the biological response of irisin to long-term aerobic exercise, we used data that come from a randomized, single-blind, singlecentre, parallel-group, non-inferiority trial previously published that compares the efficacy of 12-weeks of HIIT and MICT in weight loss among obese (i.e., BMI between 30 and 55 kg/m 2 ) healthy adults (≤50 years). The study design and the main findings concerning the primary objective of the original study has been already published [25]. Briefly, the study was performed at the Exercise Physiology Laboratory of the University of Udine, Italy, between September 2017 and June 2018.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…the most studied form of exercise regime in obesity management [8]. However, MICT requires higher volume to induce a reduction In Body Weight (BW), therefore High Intensity Interval Training (HIIT) was introduced as a time saving alternative for weight control [9].…”
Section: Moderate Intensity Continuous Training (Mict) Ismentioning
confidence: 99%